2020
DOI: 10.3892/ijmm.2020.4772
|View full text |Cite|
|
Sign up to set email alerts
|

Circular RNA CSNK1G1 promotes the progression of osteoarthritis by targeting the miR‑4428/FUT2 axis

Abstract: Osteoarthritis (OA) is a chronic disease that results in chronic arthralgia and functional disability of the affected joint. To date, there is no effective treatment available for this disease. Circular RNAs (circRNAs) are a type of intracellular stable RNA that can regulate the development and progression of OA. However, the function of circCSNK1G1 in OA has not yet been investigated. In the present study, it was found that circCSNK1G1 was upregulated in OA cartilage tissues. The upregulation of circCSNK1G1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Circular RNAs (circRNAs) are noncoding RNA molecules characterized by covalent closed loops free of 3ʹ and 5ʹ ends [ 10 ]. An increasing number of researches have suggested that novel circRNAs play various roles in osteoarthritis progression [ 11 ], such as CircCDH13 [ 12 ], circCSNK1G1 [ 13 ], circ_0128846 [ 14 ], etc. Has_circ_0005567 was first reported as osteoarthritis-related circRNA [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Circular RNAs (circRNAs) are noncoding RNA molecules characterized by covalent closed loops free of 3ʹ and 5ʹ ends [ 10 ]. An increasing number of researches have suggested that novel circRNAs play various roles in osteoarthritis progression [ 11 ], such as CircCDH13 [ 12 ], circCSNK1G1 [ 13 ], circ_0128846 [ 14 ], etc. Has_circ_0005567 was first reported as osteoarthritis-related circRNA [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…We also found that the expression of most circRNAs was upregulated, while a few were downregulated in OA. According to Wang et al [ 31 ], circRNA RNF121 aggravated the progression of OA via the miR-665/MYD88 axis (MYD88 is the canonical adaptor for inflammatory pathway), and according to Xiao et al [ 33 ], circRNA CSNK1G1 promotes the progression of OAs by targeting the miR-4428/FUT2 (fucosyltransferase) axis. Jiang et al [ 35 ] demonstrated that circRNA DHRS3 accelerates OA progression via miR-183-5p/GREM1 ( Gremlin , the miR-183-5p target gene).…”
Section: Discussionmentioning
confidence: 99%
“…Xiang et al [54] revealed the expression profile of circRNAs in OA through RNA sequencing and identified 122 cir-cRNAs of differential expression. Based on these studies, NT5C2 [8], DUSP5 [9], UBE2G1 [10], GCN1L1 [11], HIPK3 [12], VCAN [13], ASH2L [15], SEC24A [18], PRKCH [19,20], TMBIM6 [21], VWF [23], PLOD1 [23], COL6A3 [23], hsa_circ_7 [24,25], ATP9B [26], PSM3 [27], MSR [28], CDR1 [29], CDH13 [30], RNF121 [31], CSNK1G1 [33], DHRS3 [35], PTPRA [38], IQGAP1 [39], SCAPER [39], RP11-909M7.3 [39] , RSU1 [40] SERPINE2 [7,32], CDK14 [14], PDE4D [16], ANKRD36 [17], hsa_circ_9119 [22], EPS15 [26,34], ADAMTS6 [36], UNK [37,41] BioMed Research International VWF (hsa_circ_0025119) had the highest value (Figure 3, Tables 3 and 4), indicating a significant interaction between VWF and other circRNAs; also, additional functions and signaling pathways were detected in the BP. Therefore, we speculated that VWF (hsa_circ_0025119) is more feasible to be used as a...…”
Section: 2mentioning
confidence: 99%
“…It was recently demonstrated that circC-SNK1G1 upregulation is also associated with ECM degradation. circCSNK1G1 and fucosyltransferase 2 (FUT2) induce ECM degradation and chondrocyte apoptosis; miR-4428 targets FUT2 mRNA to inhibit its expression, reversing the negative effects of circCSNK1G1 and FUT2 (43). CircCSNK1G1 was upregulated in OA affected cartilage, which can induce chondrocyte apoptosis and EMC degradation through sponging mir-4428 targets.…”
Section: Roles Of Circrnas In Oamentioning
confidence: 99%